2004
DOI: 10.1002/jbm.b.30176
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the radiopacifier in an acrylic bone cement on its mechanical, thermal, and physical properties: Barium sulfate‐containing cement versus iodine‐containing cement

Abstract: In all acrylic bone cement formulations in clinical use today, radiopacity is provided by micron-sized particles (typical mean diameter of between about 1 and 2 microm) of either BaSO(4) or ZrO(2). However, a number of research reports have highlighted the fact that these particles have deleterious effects on various properties of the cured cement. Thus, there is interest in alternative radiopacifiers. The present study focuses on one such alternative. Specifically, a cement that contains covalently bound iodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Taken together, these results suggest that the copolymer is formed by blocks of pMMA intercalated by some units of TIBOM. Several authors have tried other iodinated acrylic monomers to increase radio-opacity, specifically 2-[4-iodobenzoyl]-oxo-ethylmethacrylate [17], 2,5-diiodo-8-quinolyl methacrylate [15] and 3,5-diiodine salicylic methacrylate [9], and also the addition of iodinated molecules dissolved in the cement, such as odixanol, iohexol and iohexol acetate [16]. The radio-opacity obtained with TIBOM is obtained with a smaller amount of monomer since it contains three atoms of iodine.…”
Section: Characterization Of the Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results suggest that the copolymer is formed by blocks of pMMA intercalated by some units of TIBOM. Several authors have tried other iodinated acrylic monomers to increase radio-opacity, specifically 2-[4-iodobenzoyl]-oxo-ethylmethacrylate [17], 2,5-diiodo-8-quinolyl methacrylate [15] and 3,5-diiodine salicylic methacrylate [9], and also the addition of iodinated molecules dissolved in the cement, such as odixanol, iohexol and iohexol acetate [16]. The radio-opacity obtained with TIBOM is obtained with a smaller amount of monomer since it contains three atoms of iodine.…”
Section: Characterization Of the Copolymersmentioning
confidence: 99%
“…Several authors have proposed the use of copolymers containing monomers with covalently bound iodine, which ensure radio-opacity, in the preparation of radio-opaque cements or embolization beads [14][15][16][17][18][19][20][21]. Iodine is known to be radio-opaque due to its high atomic weight (relative atomic mass = 127).…”
Section: Introductionmentioning
confidence: 99%
“…3,[8][9][10] The extent of porosity within the cement mantle is influenced by different factors including the formulation of the cement, the method of mixing, the technique of injection and the surface properties of the implant. Great efforts have been made to optimise cement formulation, [11][12] to improve mixing and/or injection, 13-15 and to select the best texture for the surface of the implant. 16,17 Despite these efforts, some degree of porosity can still be observed in bone cement mantles.…”
mentioning
confidence: 99%
“…New iodine-containing bone cements showed increased fatigue resistance 96 and decreased thermal necrosis. 97 It was also proved that iodine-cement and BaSO 4 -cement showed analogous cytocompatibility throughout every in vitro experiments. 98 Despite Hernández et al 99 reported that acrylic bone cement containing 10% bismuth salicylate in the liquid phase had overall good properties (thermal, mechanical and rheological properties) and optimum homogeneity and radiopacity, nanotechnology is a more attractive alternative to obtain reinforced composite materials due to strong interfacial interactions between the nanostructured fillers and the polymer matrix.…”
Section: Nanoparticles To Enhance Acrylic Bone Cements Performancementioning
confidence: 95%